Assessment and Mapping of Soil Organic Carbon Pool through Geo-Informatics Approach in Bhatkal Taluka of Uttar Kannada District of Karnataka - Koppad, A. G.; Janagowdar, B. S. (Indian Forester, 2017)
The research study was conducted in Bhatkal taluka of Uttar Kannada district, Karnataka, India to assess the soil organic carbon pool under different land uses. The IRS P6 LISS-III image was classified with supervised classification using ERDAS software based on ground truth data collected with the help of GPS. The land use land cover classes were dense forest, sparse forest, agriculture and open land. The soil samples up to one meter depth were drawn from different land use land cover classes. The total area under four land use classes was 31585.74 ha having SOC pool of 5.68 million tones. The dense forest cover was having maximum area (17559.5 ha) with SOC pool of 3.768 million tones. Dense forest soil sequestered higher SOC (214.58 t/ha) and agriculture land sequestered the least (78.34 t/ha). The carbon mitigation potential of the soils under dense forest was 2.74 times higher when compared to agricultural land followed by horticulture plantation (2.30 times).